Determinants of Energy Consumption in MIST Countries - Yessymkhanova, Zeinegul; Azretbergenova, Gulmira; Mukhiddinova, Salima (International Journal of Energy Economics and Policy, 2024)
In this study, the factors that determine energy consumption are tried to be explained. For this purpose, the factors determining energy consumption are analyzed specifically for MIST (Mexico, Indonesia, South Korea and Turkey) countries, for a period covering the years 2000-2022. In the study, population growth rate, balance of trade in goods and services, GDP, foreign direct investments and energy prices are used as factors determining energy consumption. The results show that the total population growth rate and GDP tend to have a positive impact on energy consumption at the 99% confidence level, while trade openness and foreign direct investments variables affect energy consumption at the 90% confidence level, and this balance exhibits a positive interaction. No significant effect of energy prices on energy consumption was detected.